2019
DOI: 10.5664/jcsm.8030
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Sleep Behaviors in a National Sample of Adolescents Followed Into Young Adulthood

Abstract: Study Objectives: Sexual minority adolescents experience mental and physical health disparities attributable to increased discrimination and minority stress. These same factors may also impair sleep health, although available literature on this topic is limited. This study examined longitudinal associations between adolescent sexual minority status and seven sleep behaviors in young adulthood and tested depressive symptoms and overweight as mediators. Method: Data were drawn from Waves 2 (11th grade) to 7 (4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…Although most previous studies in western countries used a single item to evaluate sleep quality or sleep difficulties, the trend of increased risk of sleep problems among sexual minorities was in line with this study, regardless of whether for adolescents or adults (Caceres and Hickey, 2020;Crawford and Ridner, 2018;Duncan et al, 2018;Chen and Shiu, 2017;Dai et al, 2020;Blosnich et al, 2013). The current research conclusions on sleep time and sleep delay are still inconsistent (Luk et al, 2019), which may be caused by different evaluation indexes, grouping standards and statistical description methods. More research on sleep problems of sexual minorities is needed.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although most previous studies in western countries used a single item to evaluate sleep quality or sleep difficulties, the trend of increased risk of sleep problems among sexual minorities was in line with this study, regardless of whether for adolescents or adults (Caceres and Hickey, 2020;Crawford and Ridner, 2018;Duncan et al, 2018;Chen and Shiu, 2017;Dai et al, 2020;Blosnich et al, 2013). The current research conclusions on sleep time and sleep delay are still inconsistent (Luk et al, 2019), which may be caused by different evaluation indexes, grouping standards and statistical description methods. More research on sleep problems of sexual minorities is needed.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous research (Cheng et al, 2012;Madrid-Valero et al, 2017), females had a higher risk of poor sleep quality. This study found that the mediating effects of depressive symptoms in the association between sexual orientation and sleep quality were not moderated by sex, which is different from a longitudinal study resulting from that sexual minority status was associated with daytime sleepiness through depressive symptoms only found in female (Luk et al, 2019). However, our findings were similar to a previous study that reported no sex differences in the effects of sexual minority status on sleep quality through interpersonal problems (Patterson et al, 2018).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Regarding daytime sleepiness specifically, a meta-analysis indicated that depressive symptoms were positively associated with daytime sleepiness among adolescents (O'Callaghan et al, 2021). Furthermore, in a national longitudinal study of U.S. youth, sexual minority female adolescents reported greater depressive symptoms compared to their heterosexual peers, which in turn predicted more frequent daytime sleepiness (Luk et al, 2019). Therefore, higher depressive symptoms among sexual and racial minority people may lead to more daytime sleepiness.…”
Section: Depressive Symptoms and Sleepmentioning
confidence: 99%